2020
DOI: 10.1016/j.cell.2020.08.039
|View full text |Cite
|
Sign up to set email alerts
|

pH-Gated Succinate Secretion Regulates Muscle Remodeling in Response to Exercise

Abstract: Highlights d Mouse and human muscle selectively release succinate during exercise d Muscle cells release succinate by pH-gated secretion via MCT1 d Extracellular succinate regulates paracrine responses to exercise through SUCNR1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
144
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 83 publications
4
144
0
3
Order By: Relevance
“…Thus, additional factors likely influence SUCNR1 expression in PPGL tissue. Potentially, tumor tissue pH and monocarboxylate transporter 1 expression level play an essential role, as these highly likely determine succinate release to the extracellular space (20,21). Of note, hypoxia or HIF activation positively regulate monocarboxylate transporter 1 expression [summarized in (55)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, additional factors likely influence SUCNR1 expression in PPGL tissue. Potentially, tumor tissue pH and monocarboxylate transporter 1 expression level play an essential role, as these highly likely determine succinate release to the extracellular space (20,21). Of note, hypoxia or HIF activation positively regulate monocarboxylate transporter 1 expression [summarized in (55)].…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in succinate levels arise during hypoxia/ischemia, hyperglycemia, due to tissue damage, or at sites of inflammation [summarized in (19)]. More recently, pH dependent transport of succinate from intact cells via monocarboxylate transporter 1 has been shown in an ischemia reperfusion model of the heart and following exercise under acidic conditions (20,21). An apparent function of SUCNR1 is the activation of coping mechanisms upon adverse conditions, including stimulation of proliferation of different cell types, migration, and angiogenesis (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 10, 2021. ; https://doi.org/10.1101/2021.02.10.430650 doi: bioRxiv preprint 10 al., 2000). The transporters for succinate have not been fully characterized, and in addition to plasma membrane dicarboxylate transporters (Kaufhold et al, 2011), MCT1 can also export succinate (Prag et al, 2020;Reddy et al, 2020). This may apply to other MCTs as well.…”
Section: Discussionmentioning
confidence: 99%
“…The current state of the literature suggests that exogenous succinate is not imported into most cells (Clerc & Polster, 2012;Ehinger et al, 2016;MacDonald et al, 1989;Protti, 2018), despite widespread expression of monocarboxylate and dicarboxylate transporters capable of carrying succinate across the plasma membrane (Andrienko et al, 2017;Nakai et al, 2006;Pajor, 2014;Prag et al, 2020;Reddy et al, 2020). Brown adipose tissue is thought to be the main sink for succinate, allowing it to fuel thermogenesis (Mills et al, 2018).…”
Section: δ ρmentioning
confidence: 99%
“…Recent work has shown that pH gated release of succinate is a myokine involved in adaptive responses to exercise [45]. Others have shown that peroxiredoxins and thioredoxins are released into the blood plasma compartment in an intensity and time dependent manner in response to high intensity, but not moderate intensity exercise in humans [26].…”
Section: Discussionmentioning
confidence: 99%